On Some Integral Operators for Certain Classes of p-Valent Functions - Lokesh Vijayvargy; Pranay Goswami; Bushra Malik (International Journal of Mathematics and Mathematical Sciences)
We study some generalized integral operators for the classes of p-valent functions with bounded radius and boundary rotation. Our work generalizes many previously known results. Many of our results are best possible.